Biodegradation of microplastic in batch culture and continuous reactor for bio-diversity conservation / Nur Aliah Ahmad Tarmizi - Ahmad Tarmizi, Nur Aliah (2022)
Currently, microplastic is considered a major concern worldwide and noteworthy among the researcher and authorities. Microplastic has spread ubiquitously in the environment, particularly in the aquatic system, due to its smaller size (size less than 5mm). This tiny microplastic adversely affected the environment, notably aquatic life via ingestion, choking, and entanglement. This microplastic is arduous to degrade as it takes a thousand years due to the properties of plastic itself and consequently remains in nature. This research study aims to investigate the performance of four (4) types of microplastics in a closed system: polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), and polystyrene (PS). This microplastic has been biodegraded in the batch culture system using a colony of bacteria acquired from landfill leachate as a carbon source. The percentage of microplastic removal after the incubation period (7, 14, and 21 days) in batch culture was determined. In addition, the analysis of chemical properties, morphology surfaces of the microplastic, and ammonia-nitrogen for each batch culture were evaluated. The findings revealed that all microplastic could be degraded based on the percentage weight loss, chemical structure changes, surface morphology, and ammonia-nitrogen removal under the nitrification process after the incubation period. PE microplastic showed the highest percentage weight loss (8.8%) compared with other microplastic. Analysis by Fourier-transform infrared spectroscopy (FTIR) demonstrates that the chemical structure of each polymer has changed, which involved the formation of a new peak after the incubation periods. The chemical bond of C=O has formed in PP and PE, C-H has been developed in PS, and O-H has emerged in PET. The observation by scanning electron microscope (SEM) indicated the alteration on the surface in each microplastic, such as fractures and rough surfaces. Besides that, PP microplastic indicated the maximum ammonia-nitrogen removal after 16 days incubation period (97.41%). Next, the performance of the continuous reactor of continuous culture in removing the PE microplastics and ammonia nitrogen with different dilution rates was evaluated. The findings based on FTIR analysis show the absorption peaks at 1540 and 1635cm-1 attributed to C=C has experienced elongation after the changes of flow rate of 20 rpm to 30 rpm due to the exposure and interaction between microorganism colony and microplastic. This research study indicates that microplastics could be reduced in the batch culture using leachate inoculum and the continuous culture reveals a capability in degrading PE microplastic with the changes of chemical structure. This study also found that the activity of the microorganism’s population plays a significant role in the degradation of microplastic. Furthermore, extending the incubation period for microplastic biodegradation can attain better optimal results in further research.